A Study of Member Displacement According to Seasonal Climate of the Sungnyemun Gate, a Korean Wooden Architectural Heritage Site - Hyowon Seo; Hana Lee; Sunghan Kim (Buildings)
This study analyzes the results of a displacement measurement of the Sungnyemun Gate’s structural members, such as column, girder, and hip rafter, carried out by the National Institute of Cultural Heritage for about 10 years from December 2013 to October 2022. Through this, we attempt to examine the behavior of wooden architectural heritage sites according to seasonal changes and infer the factors influencing structural deformation. As a result of the analysis, it was confirmed that the structural members of the Sungnyemun Gate, including the columns, girders, and hip rafters, continued to move and that the displacement of members was accumulated, and the structure was deformed. It was also confirmed that member displacements accumulated in a specific direction. In the case of the Sungnyemun Gate, the column leaning south, the hip rafters’ endpoint sagging, and the girders’ center deflecting were continuously observed. Furthermore, the behavior of wooden architectural heritage sites, where displacement accumulates as it undergoes repeated deformation and recovery according to seasonal changes, was also revealed in detail. The deformation of the Sungnyemun Gate’s members shows a pattern that reflects the mechanical properties of wood, which repeatedly increases and decreases displacement depending on the season. However, seasonal deformation did not appear the same in all the members. Even the same member has an uneven drying speed due to differences in the amount of sunlight it receives depending on its location, which leads to uneven distribution of deformation. The significance of this study is that it examined the behavior of a wooden architectural heritage site in detail based on the quantitative results of long-term measurements and prepared primary data for the future management of wooden architectural heritage sites.